INDICES OF MORTALITY OF OCCUPATIONAL PATIENTS AS THE CRITERION OF QUALITY OF THE SYSTEM OF GIVING OCCUPATIONAL PATHOLOGICAL HELP TO WORKING POPULATION - T. E. Piktushanskaya (Acta Biomedica Scientifica, 2012)
Analysis of dynamic rows of indices of occupational patients mortality in coal mining industry for the period from 1950 till 2009 (8078 cases) has been carried out. Essential increase of age and the length of service of workers taken into registration for the first time in the Centre of Occupational Pathology as well as the reduction in seven times of the period of living of occupational patients from the moment of establishing the diagnose of an occupational disease till death have been revealed. It has been shown that the urgent working out and realization. of the complex system of medical rehabilitation of workers with initial indications of influence of harmful factors of working environment to the organism as well as with initial symptoms of occupational diseases are demanded in the country.